From graphite oxide to highly water dispersible functionalized graphene by single step plant extract-induced deoxygenation - Mhamane, Dattakumar; Ramadan, Wegdan; Fawzy, Manal; Rana, Abhimanyu; Dubey, Megha; Rode, Chandrashekhar; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra (Green Chemistry, 2011)
We report a single step facile synthesis of highly water dispersible functionalized graphene nanosheets by plant extract-induced deoxygenation of graphite oxide (GO). The results of various characterizations reveal that the properties of such plant extract-converted graphene nanosheets (PCGN) are comparable to chemically converted graphene nanosheets (CCG). These results open a green route to the emerging graphene-based technologies.

Indanthrone derived disordered graphitic carbon as promising insertion anode for sodium ion battery with long cycle life - Suryawanshi, Anil; Mhamane, Dattakumar; Nagane, Satyawan; Patil, Shankar; Aravindan, Vanchiappan; Ogale, Satishchandra; Srinivasan, Madhavi (Electrochimica Acta, 2014)
We report facile, one step synthesis of disordered graphitic carbon by high temperature (1000 degrees C) pyrolysis of indanthrone dye (ID). The pyrolysed carbon is disordered in nature and the same is clearly evidenced by various analytical techniques like X-ray diffraction, Raman spectroscopy and high resolution transmission electron microscopy. Na-insertion properties of such indanthrone dye derived disordered graphitic carbon (IDDGC) is evaluated in half-cell assembly (Na/IDDGC). The test cell delivered a reversible capacity of similar to 160 mAh g(-1) at current density of 25 mAg 1. In addition, excellent cycling profiles are noted for such IDDGC, which retains 67% of initial reversible capacity after 500 cycles. The present study clearly highlights the importance of disorder in the graphitic carbon for efficient Na-ion storage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: anode; disordered carbon; indanthrone; Na-ion battery

Large scale synthesis of graphene quantum dots (GQDs) from waste biomass and their use as an efficient and selective photoluminescence on-off-on probe for Ag+ ions - Suryawanshi, Anil; Biswal, Mandakini; Mhamane, Dattakumar; Gokhale, Rohan; Patil, Shankar; Guin, Debanjan; Ogale, Satishchandra (Nanoscale, 2014)
Graphene quantum dots (GQDs) are synthesized from bio-waste and are further modified to produce amine-terminated GQDs (Am-GQDs) which have higher dispersibility and photoluminescence intensity than those of GQDs. A strong fluorescence quenching of Am-GQDs (switch-off) is observed for a number of metal ions, but only for the Ag+ ions is the original fluorescence regenerated (switch-on) upon addition of L-cysteine.

Surfactant free gram scale synthesis of mesoporous Ni(OH)(2)-r-GO nanocomposite for high rate pseudocapacitor application - Singh, Upendra; Banerjee, Abhik; Mhamane, Dattakumar; Suryawanshi, Anil; Upadhyay, Kush Kumar; Ogale, Satishchandra (RSC Advances, 2014)
We report a single-step surfactant-free gram scale hydrothermal synthesis of mesoporous Ni(OH)(2) nanoparticles and the Ni(OH)(2)-reduced graphene oxide (Ni(OH)(2)-r-GO) nanocomposite. Interesting morphological features are noted. These nanomaterials are examined and compared as cathode materials for pseudo-capacitor application through detailed characterizations. A high specific capacitance (C-s) of 1538 F g(-1) is observed for Ni(OH)(2)-r-GO even at a high current density of 40 A g(-1), whereas at the same current rate, bare Ni(OH)(2) shows C-s of only 936 F g(-1).

Triple nanocomposites of CoMn2O4, Co3O4 and reduced graphene oxide for oxidation of aromatic alcohols - Jha, Ajay; Mhamane, Dattakumar; Suryawanshi, Anil; Joshi, Sameer M.; Shaikh, Parvez; Biradar, Narayan S.; Ogale, Satishchandra; Rode, Chandrashekhar V. (Catalysis Science & Technology, 2014)
A composite of reduced graphene oxide (RGO) with oxides of manganese and cobalt together was prepared by a solvothermal method. During synthesis, both the reduction of graphene oxide as well as the growth of nanorod shaped CoMn2O4 and Co3O4 occurred simultaneously having a crystallite size of similar to 8 nm calculated from X-ray diffraction (XRD). The as-obtained triple nanocomposite material designated as RGO-MnCoO exhibited excellent activity for the liquid phase aerobic oxidation of aromatic alcohols under base-free conditions selectively giving the corresponding aldehydes (>85%). RGO loading was varied in the range of 1-10%, among which 1% RGO-MnCoO showed maximum catalytic activity enhancement of 24% as compared to the bare mixed oxide (MnCo-MO) for the oxidation of vanillyl alcohol. HR-TEM of RGO-MnCoO revealed that it was a composite material having uniform nanotubes of similar to 25 nm length and 6 nm diameter with a fringe pattern showing the (103) and (004) planes and lattice spaces of 0.26 nm and 0.22 nm, respectively, for the spinel CoMn2O4. The detailed studies on the morphology, size and composition of the as-prepared RGO-MnCoO nanocomposite by XRD, XPS, N-2-adsorption/desorption and O-2-TPD techniques were used to understand the role of RGO in the enhancement of catalytic activity for oxidation reaction.

Graphene based nanocomposites for alloy (SnO2), and conversion (Fe3O4) type efficient anodes for Li-ion battery applications - Mhamane, Dattakumar; Aravindan, Vanchiappan; Taneja, Divya; Suryawanshi, Anil; Game, Onkar; Srinivasan, Madhavi; Ogale, Satishchandra B. (Composites Science and Technology, 2016)
Two types of trigol reduced one pot synthesized graphene (TRG) based nanocomposites (SnO2-TRG, and Fe3O4-TRG) are examined as potential anodes for Lithium ion battery (LIB) applications. The two specific systems represent different electrode reaction mechanisms, namely alloying, and conversion respectively. The high resolution transmission electron microscopy (HR-TEM) analysis confirms the uniform distribution of SnO2 (similar to 2 nm), and Fe3O4 (similar to 8 nm) particulates on ultrathin TRG nanosheets and highlights the importance of surfactant free synthesis. The SnO2-TRG, and Fe3O4-TRG exhibited the maximum reversible capacity of similar to 947, and similar to 1024 mA h g(-1), respectively. The results show that such graphene based composite materials can be effectively used as prospective anodes for LIB applications. (C) 2016 Elsevier Ltd. All rights reserved.